Pemberian Pakan Serat Sisa Tanaman Pertanian (Jerami Kacang Tanah, Jerami Jagung, Pucuk Tebu) Terhadap Evolusi pH, N-NH3 dan VFA Di dalam Rumen Sapi - Yunasri Usman (Jurnal Agripet, 2013)
(Feeding agricultural crop residues (groundnut straw, corn straw, sugarcane straw) to the pH evolution, N-NH3 and VFA in the cow rumen)ABSTRACT. The goal of this study is to evaluate the condition of fermentation in the rumen of cows by administration of 3 types of feed fiber agricultural crop residues (Groundnut Straw (GS), Corn Straw (CS) and Sugarcane Tops (ST)). Single feeding wascarried out at 2 Holstein Friesian Crossbred (HFC) cows with the age of 4-5 by fistula rumen.This study was conducted 20 days and with a 14-dayadaptation period.At the end of the adaptation period, rumen fluid was collected to measure pH, N-NH3and VFA based on feed treatment percow.Collection of rumen fluid was simultanous conducted for 24 hours at 27 time points decision.The results of the experiment showed that the level of pH for GS, CS and ST was 7.02 + 0.29; 6.54 + 0.16 and 6.54 + 0.14 respectively. The level of N-NH3 was 4.90 + 2.10 mg/100 ml of rumen fluid; 7.36 + 3.10 mg/100 ml of rumen fluid; 2.26 + 0.85 mg/100 ml of rumen fluidfor GS, CS and ST, respectively. Meanwile, the level of VFA was 57.44 + 12.75 mmol/l ml, 64.84 + 10.82 mmol/l and 44.13 + 6.66 mmol/l ml of rumen fluid, respectively.